Needs Analysis on Tourism Pocket Books for POKDARWIS Kemiren Banyuwangi - M. Thoha Thobibi; Niken Nur Hafifa; Nayla Sofiatun Nafisa; Widya Putri Lestari; Wiwin Indiarti (Jurnal Bina Ilmu Cendekia, 2025)
Kemiren is known as a cultural tourism village in Banyuwangi Regency and is included in the Ijen UNESCO Global Geopark area. Despite its significant tourism potential, the tourism awareness group (Pokdarwis) still lacks practical supporting media that can assist tour guides, particularly when interacting with international tourists. This study aims to analyze the needs for a tourism pocket book by identifying the gap between the ideal and the existing conditions of tourism information media used in Kemiren Village. The study employed a descriptive qualitative design. Data were collected through questionnaires and documentation involving 20 members of Pokdarwis Kemiren as respondents. The questionnaire examined several aspects related to the tourism pocket book, including content, theme selection, visualization, and language use. The collected data were analyzed using the interactive analysis model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that there is a significant gap between the expected condition and the existing condition because Kemiren Village does not yet have a tourism pocket book that can be used as a practical guide during tourism activities. The respondents expect the pocket book to contain clear and comprehensive information about cultural tourism in Kemiren, such as traditional rituals, culinary traditions, traditional houses, local arts, and community life. In addition, the pocket book is expected to include attractive visual elements such as photographs, illustrations, and maps, as well as a well-organized layout to facilitate understanding. The language used should be simple, clear, and presented in bilingual form (Indonesian and English) in order to support communication with international tourists. Therefore, this study concludes that the development of a tourism pocket book is highly necessary to support tourism management and improve the effectiveness of cultural tourism promotion in Kemiren Village.